Emergency frequency control strategy of distribution system based on the coordination of multi-resource - Shen, Zeyuan; Wang, Chao; Wang, Yao; Zhao, Haibo; Wu, Zhong; Hu, Ende (Frontiers in Energy Research, 2023)
Introduction: The urban distribution system plays a crucial role in efficient power distribution within urban areas. The increasing frequency and intensity of extreme events in recent years pose significant challenges to the reliable operation of urban distribution systems. While extensive research focuses on emergency frequency control strategies for large-scale power grids, there is a need for targeted attention to address the emergency frequency control challenges arising when the urban distribution system becomes isolated from the superior power grid due to extreme events. Methods: This paper aims to enhance the system's resilience to extreme events by investigating the coordinated regulation of various resources within the urban distribution system. The studied resources include synchronous generators, wind farms, battery energy storage systems, temperature control loads, and conventional load resources. A reduced-order model for the multi-resource system’s frequency response is established. Analytical expressions for key parameters, including the lowest system frequency, lowest point time, and quasi-steady state frequency, are derived. Results: To address the challenge of multi-resource coordinated regulation, an emergency frequency control strategy is proposed. This strategy takes into account the system safety frequency constraint, resource control amount constraint, and line power flow constraint. Simulations are conducted using the MATLAB/Simulink platform, considering IEEE 13 bus and IEEE 33 bus distribution systems as test cases. Discussion: Simulation results demonstrate the effectiveness of the proposed method in regulating the distribution system's resources, ensuring that the lowest frequency remains within the safety threshold of 49.8 Hz. Moreover, the proposed method minimizes control costs and limits load shedding, thereby fully leveraging the capabilities of diverse resources in the urban distribution system. This research contributes valuable insights into addressing emergency frequency control challenges in urban distribution systems during extreme events.